Analysis of the Implementation of the Government Internal Control System (SPIP) in the Tebing Tinggi City Government - Dito Aditia Darma Nasution; Yohana Ewicha Br Harianja; Lasmian Panjaitan; Hairani Siregar; Tri Putrianis Laia (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the implementation of the Government Internal Control System (Sistem Pengendalian Intern Pemerintah/SPIP) in the Tebing Tinggi City Government and to assess the alignment between normative regulations and practical implementation in local government administration. This study employs a qualitative research design with a case study approach. Data were collected through document analysis of laws and regulations, SPIP evaluation reports, audit reports, performance reports, and other relevant supporting documents. Data analysis was conducted by comparing SPIP implementation standards as stipulated in Government Regulation Number 60 of 2008 with the actual conditions of implementation in the Tebing Tinggi City Government, based on the five elements of SPIP: control environment, risk assessment, control activities, information and communication, and monitoring. The findings are expected to provide empirical evidence on the level of SPIP implementation and identify key challenges in its application, serving as a basis for formulating strategic recommendations to strengthen internal control systems in order to enhance accountability and improve the quality of local government governance.